NURSE’S ROLE IN PAIN MANAGEMENT: A CASE STUDY OF SCHOOL-AGED CHILDREN WITH CANCER - Pakdeto, Rose (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
Children with cancer always confront pain from their disease, procedures, and cancer treatments, which results in the suffering of both patients and their families. The nurse’s role in pain management is to relieve patients’ pain and their family’s anxiety. The symptom management model of Dodd is used to take care of pain in school-aged children who can’t manage their symptoms by themselves. This model helps to relieve and reduce the pain experience that affects psychological health in the children, and assists their families to be able to manage their children’s pain. Consequently,the nursing concept of symptom management explains how to care of the patient when it is applied to school-age children with cancer, it was able to help completely assessing the children’s symptoms, such as pain experience, pain management method, and the result to provide the all-around information assisting the evaluation of children patients with cancer to have better management resulting in more efficient pain treatment.